Forward backward domain decomposition method for finite element solution of electromagnetic boundary value problems - Ozgun, Ozlem; Kuzuoglu, Mustafa (Microwave and optical technology letters, 2007)
We introduce the forward–backward domain decomposition method (FB‐DDM), which is basically an improved version of the classical alternating Schwarz method with overlapping subdomains, for electromagnetic boundary value problems. The proposed method is noniterative in some cases involving smooth geometries, or it usually converges in a few iterations in other cases involving challenging geometries, via the utilization of the locally‐conformal PML method. We report some numerical results for two‐dimensional electromagnetic scattering problems. © 2007 Wiley Periodicals, Inc. Microwave Opt Technol Lett 49: 2582–2590, 2007; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.22757